1982
DOI: 10.1126/science.7134983
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Event-Related Potential Manifestations of Information Processing Stages

Abstract: The timing of two event-related potential components was differentially affected by two experimental variables. The earlier component (NA) was affected by degradation of the stimuli and the later component (N2) by the nature of a classification task. The results support the hypothesis that NA and N2 reflect sequential stages of information processing, namely, pattern recognition and stimulus classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 263 publications
(106 citation statements)
references
References 10 publications
4
101
1
Order By: Relevance
“…In addition, the delay of visual N2 was not due to a delay of the preceding NA, although NAis known to occur in the latency range of the N2 peak of the ERP (8,9). NAand N2 reflect sequential stages of information processing, namely, pattern recognition and stimulus classification (8). The peak latency of N2 varies as a function of the difficulty of discrimination, and precedes and correlates with the timing of discriminative behavioral responses (9).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the delay of visual N2 was not due to a delay of the preceding NA, although NAis known to occur in the latency range of the N2 peak of the ERP (8,9). NAand N2 reflect sequential stages of information processing, namely, pattern recognition and stimulus classification (8). The peak latency of N2 varies as a function of the difficulty of discrimination, and precedes and correlates with the timing of discriminative behavioral responses (9).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the visual N2 latency was delayed in patients with multiple lacunar infarcts. In addition, the delay of visual N2 was not due to a delay of the preceding NA, although NAis known to occur in the latency range of the N2 peak of the ERP (8,9). NAand N2 reflect sequential stages of information processing, namely, pattern recognition and stimulus classification (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations